2022
DOI: 10.3390/ijerph19010506
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Higher Quality of Systematic Reviews Addressing Nutrition and Cancer Prevention

Abstract: Systematic reviews/meta-analyses (SR/MAs) are considered a reliable source of information in healthcare. We aimed to explore the association of several characteristics of SR/MAs addressing nutrition in cancer prevention and their quality/risk of bias (using assessments from AMSTAR-2 and ROBIS tools). The analysis included 101 SR/MAs identified in a systematic survey. Associations of each specified characteristic (e.g., information about the protocol, publication year, reported use of GRADE, or other methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies showed that involving librarians or information specialists may improve the reproducibility of literature searches (Koffel, 2015; Rethlefsen et al, 2015) and may be associated with a lower risk of bias of the SRs as shown in a small sample (Aamodt et al, 2019). Another study showed that including information about the search for unpublished studies is related to the methodological quality of SRs (Storman et al, 2022). The fact that the search strategy item is also included in the Rapid Appraisal FFT additionally highlights the role of a high-quality literature search on the overall quality appraisal of SRs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that involving librarians or information specialists may improve the reproducibility of literature searches (Koffel, 2015; Rethlefsen et al, 2015) and may be associated with a lower risk of bias of the SRs as shown in a small sample (Aamodt et al, 2019). Another study showed that including information about the search for unpublished studies is related to the methodological quality of SRs (Storman et al, 2022). The fact that the search strategy item is also included in the Rapid Appraisal FFT additionally highlights the role of a high-quality literature search on the overall quality appraisal of SRs.…”
Section: Discussionmentioning
confidence: 99%
“…Urology is a rapidly expanding field, with many new management approaches and innovative technologies. To appraise such advances, compare the effectiveness of procedures and their side effects, or alternatively, to evaluate etiology, estimate prevalence, assess diagnosis or prognosis, systematic reviews/meta-analyses (SRs/MAs) are considered as a reliable source of information and evidence [ 1 ]. SRs/MAs assume the top position pertaining to the quality and dependability of the evidence generated, and are a reliable information source [ 2 ].…”
Section: Introductionmentioning
confidence: 99%